POLA INTERAKSI GURU DENGAN PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA DAAR EL HASANAH JAWILAN SERANG - Hasanah, Neneng; Muhajir, Muhajir (Risâlah, Jurnal Pendidikan dan Studi Islam, 2022)
The interaction of teachers with students is a necessity in the learning process in schools, which impacts their learning outcomes and achievements at school. This study aims to analyze the interaction pattern between teachers and students in learning Islamic religious education. The research uses a qualitative descriptive method with a pedagogical and sociological approach. The study results reveal that the pattern of interaction between teachers and students in learning Islamic religious education occurs in three directions: teacher-student-student. Furthermore, the research findings suggest that teachers can interact with a three-way pattern to arouse students' motivation and interest in learning.